A MULTI-DOMAIN FRAMEWORK FOR MODELLING EDUCATIONAL GAMES: TOWARDS THE DEVELOPMENT OF EFFECTIVE EDUCATIONAL GAMES - ,, MIFRAH AHMAD (2015)
A game-based learning allows leveraging on young learners preference towards playing games to turn games into tools for learning. The complex nature of an educational game that covers various knowledge domains such as learning theories, the subject being thought and the gaming activities warrants for modeling to be part of the educational game development such that effectiveness of the educational game can be better ensured. In relation to that, a framework consisting of elements and their relationships ofan educational game, with the aim of highlighting how these elements relate to each other to gain effectiveness should be considered. Therefore, a systematic literature review has provided a wider aspect on the types of educational game elements, and existing frameworks and models. Hence, this study proposes a multi-domain framework with connecting elements to present implicit relationships for game developers to understand theoretical aspects of educational games.